Investigating the Impact of COVID-19 Disruption on the Decarbonisation Agenda at Airports: Grounded or Ready for Take-Off? - Peter Hemmings (MDPI AG, 2021)
COVID-19 has had wide-ranging impacts on organisations with the potential to disrupt efforts to decarbonise their operations. To understand how COVID-19 has affected the climate change mitigation strategies of Airport Operators (AOs), questionnaires and semi-structured interviews with Sustainability Managers were undertaken in late 2020 amidst a period of disruption. While all reported that COVID-19 impacted delivery of interventions and projects to mitigate climate change, the majority stated that it would not impact their long-term climate goals, such as Net Zero by 2050. The most popular climate change mitigation interventions AOs intend to deploy between now and 2030 are on-site renewables and Electric Vehicles and related infrastructure. Engineered carbon removal interventions were considered highly unlikely to be deployed in this timeframe, with potential implications for Net Zero decarbonisation pathways. Despite the severe impacts of COVID-19 on the sector, results indicate that AOs remain committed to decarbonisation, with climate change action remaining the key priority for airports. Given ongoing financial and resource constraints, AOs will need to explore new business models and partnerships and nurture collaborative approaches with other aviation stakeholders to not only maintain progress toward Net Zero but “build back better”. Government support will also be needed to stimulate the development of a sustainable, resilient, low-carbon aviation system.